Repositioning Legal Protection For Victims of Domestic Neglect In Indonesia: Between Legal Breakthroughs and Reality? - Rani Hendriana; Agus Raharjo; Baginda Khalid Hidayat Jati; Jaco Barkhuizen; Bhanu Prakash Nunna; Lintang Ario Pambudi (Kosmik Hukum, 2024)
Domestic neglect is frequently occurring yet often overlooked and considered less significant compared to physical and sexual violence. This research employs normative juridical research methods and is analyzed qualitatively through a comparative legal study approach in Indonesia, India, and South Africa. The findings reveal that there have been legal breakthroughs in terms of criminalizing domestic neglect; however, the actual legal protection for the victims does not correspond proportionately. Certain limitations within domestic neglect result in the lack of assured legal protection. Even though it is considered an ordinary offense, its effectiveness is hindered due to minimal reporting, and the provision of rights does not align with the victims' needs. This situation exists in all three countries compared in the legal comparative process, although there are aspects that can be referred to in India's regulations. Addressing this issue involves repositioning the victims by reformulating the addition of victim rights according to their needs, including negligence as an element of neglect, reformulating restitution, and transferring assets to victims as a form of criminal sanction for perpetrators, incorporating domestic neglect in law enforcement agencies' case disclosure targets and annual programs in government agencies, and reinforcing legal-cultural awareness among the community to halt the domino effect of victims suffering from domestic neglect.